Carbon dioxide laser treatment in burn-related scarring: A prospective randomised controlled trial - Douglas, H.; Lynch, J.; Harms, K.A.; Krop, T.; Kunath, L.; van Vreeswijk, C.; McGarry, Sarah; Fear, M.W.; Wood, F.M.; Murray, A.; Rea, S. (2019)
Aim: To investigate the effect of ablative fractional CO2 laser (AFCO2L) on burns scar appearance and dermal architecture at 6 weeks and up to 3-years post-treatment.